Complexities in mega rail transportation projects: "Sydney metro" and "Melbourne metro rail" insight. Issue 5 (29th November 2019) - Gharehbaghi, Koorosh; McManus, Kerry; Hurst, Neville; Robson, Kathryn; Myers, Matt
Abstract : Purpose: The purpose of this paper is to initially evaluate the most current and important complications of sustainable mega rail transportation projects. This purpose is assisted by thoroughly reviewing the foremost uncertainties and challenging issues of STI. Once these factors are established, they will be the base of STI indicators. Finally, to consolidate such alignment, the Sydney Metro and Melbourne Metro are then compared and analyzed. The analysis would then create a platform to measure sustainability and relevant complexities in mega rail transportation projects. Design/methodology/approach: To further consolidate such hypothesis, this research investigated two mega rail transportation projects in Australia. Both Sydney Metro and Melbourne Metro Rail were selected as the basis of case study, as both possess similar sustainability aspects. Findings: As an outcome this research found that, complexities in both of these projects were based on future challenges and opportunities including imperfect equalization or not balancing all the four sustainability indicators; and where and how to emphasize the overlapping of these four indicators. In summary, these findings can assist the relevant planners, to better prepare and manage mega railway infrastructure and their operations. Originality/value: While the sustainability for transportation infrastructure has been covered extensively by other authors, this paper strengthens the four specific and separate STI indicators – especially for mega rail infrastructure. Although, there are some crossover areas within these indicators, however, this research separately validates each as an independent entity. Commonly, there are three dimensions within the sustainability domain – environmental, economical and social. Nevertheless, for this research, a fourth dimension engineering which includes all the technical focus, has been separately developed. This is particularly important to effectively deal with all the complexities, particularly for mega projects, such as rail transportation infrastructure. Accordingly, separating the engineering dimension would thus reshape the triple bottom line factors to include a separate technical focus. To further evaluate this separation of the four specific areas, two mega Australian rail transportation projects are then reviewed as experiments.